ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI (STUDI PADA KANTOR PELAYANAN PAJAK SEMARANG TIMUR) - Nurul Anwariyah, 11.05.52.0203; Badjuri, Achmad (Students Journal of Accounting and Banking, 2014)
The research have purpose analysis test factors regardâs compliance personal taxpayer. Research responders that is personal taxpayer area East Semarang district and North Semarang distric. On the research using independent variable which is, administration system modernizations, taxes science, ministering quality, taxes motivation and administration sanction. Justified sampling method using a method non probality sampling with purposive sampling technique. The data using is primary data complement to have questioner from of 118 questioner publish. The research using double regret analysis to Hypothesis Test. The research output has indicated modernization administration system variable, taxes science, and ministering quality regard positive and not significance, but taxes motivation variable and administration sanction regard positive and significance to be regardâs compliance personal taxpayer.Keywords: modernization administration system, taxes science, ministering quality, taxes motivation, administration sanction, regardâs compliance personal taxpayer